Influencia de un Programa de Coordinación Dinámica General para el Desarrollo de la Psicomotricidad de Niños Entre 6 a 11 Años de Edad en Condición de Discapacidad Cognitiva Leve que Asisten al Aula de Apoyo de la Institución Educativa Antonio Nariño de Calarcá (2015)
This study aimed to determine the influence of a general dynamic coordination program for the development of motor skills in children aged 6-11 years with mild cognitive impairment who attend the classroom support the school Antonio Nariño of Calarca. It was attended by 10 students between 6 and 11 years old, students in primary grades. A pre-test to assess in principle the overall dynamic coordination and the key elements of the motor in order to implement the program and determine the influence, collecting the final data after the relevant test for correlations were performed. The results obtained were determined with test ozeretski - Guilmain where was evident that the students showed an improvement in the processes evaluated in pretest. According to the results, the CDG DCL program caused significant motor skills in learners changes, physical education classes containing diverse dynamics related to overall coordination and carried out with a minimum of four hours per week elements contribute for the development of motor skills in children of 6-11 years of age with mild cognitive impairment who attend the classroom support the Educational Institution Antonio Nariño of Calarca.